2015
DOI: 10.1039/c5tx00146c
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliferone β-d-galactopyranoside inhibits chemically induced renal carcinogenesis via alteration of oxidative stress, hyperproliferation and inflammation: possible role of NF-κB

Abstract: Umbelliferone (7hydroxycoumarin) compound possesses strong anti-inflammatory and free radical scavenging activity. The intend of the current study was to conclude the renalprotective efficacy of Umbelliferone β-D-galactopyranoside (UFG) over diethylinitrosamine (DEN) initiated and ferric nitrilotriacetate (Fe-NTA) promoted the oxidative stress, inflammation and renal injury in Wistar rats. The capacity of UFG to scavenge the reactive nitrogen species (RNS) and reactive oxygen species (ROS) was evaluated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…The Umbelliferae family is inclusive of economically important herbs, such as celery, cumin, fennel, parsley alexanders, angelica, asafoetida, and giant hogweed [9,170]. UMB possesses a variety of bioactivities, and several investigators have previously reported its in vivo antioxidant and anti-inflammatory effects and studied the underlying mechanisms of action in several animal models [30,[171][172][173][174][175]. The anticancer activity of UMB in hepatocellular [176], colon [177], and oral [178] carcinomas has been well-acknowledged.…”
Section: Urolithin Amentioning
confidence: 99%
“…The Umbelliferae family is inclusive of economically important herbs, such as celery, cumin, fennel, parsley alexanders, angelica, asafoetida, and giant hogweed [9,170]. UMB possesses a variety of bioactivities, and several investigators have previously reported its in vivo antioxidant and anti-inflammatory effects and studied the underlying mechanisms of action in several animal models [30,[171][172][173][174][175]. The anticancer activity of UMB in hepatocellular [176], colon [177], and oral [178] carcinomas has been well-acknowledged.…”
Section: Urolithin Amentioning
confidence: 99%
“…The hepatic parameters, namely alkaline phosphatase (AST), aspartate aminotransferase (AST), alanine transaminase (ALT); serum renal parameters, including blood urea nitrogen (BUN), total protein, creatinine, albumin; lipid parameters, such as total cholesterol (TC), high density lipoprotein (HDL), triglyceride (TG), very low density lipoprotein (VLDL) and, low density lipoprotein (LDL), were scrutinized using commercially available diagnostic kits. The atherogenic index and coronary risk index were scrutinized as per the given formula: [24][25][26][27][28][29][30][31] Inammatory and pro-inammatory mediators Pro-inammatory cytokines, namely interleukin-6 (IL-6), tumor necrosis factor-a (TNF-a), and inammatory mediators, such as C-reactive protein (CRP), were also estimated as per the instructions in the available commercial kits.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…The in vivo anti-inflammatory activity of umbelliferone (2), the most common natural coumarin, has recently been reported by Wang et al (2019b), showing the protective effect and underlying mechanism of action of 2 against lipopolysaccharide (LPS)-induced acute lung injury, following the similar mechanism as stated earlier. However, in fact, several researchers previously demonstrated the in vivo anti-inflammatory and antioxidant effects of 2, and associated mechanisms of actions were also studied quite extensively in various animal models (Rauf et al 2014;Anwar et al 2015;Sim et al 2015;Germoush et al 2018). The role of esculin (18) against macrophages and endotoxin shock induced by LPS in mice was analyzed by Li et al (2016a), where they showed that this glycoside could suppress inflammatory reactions in macrophages and protected mice from LPS-induced endotoxin shock.…”
Section: Anti-inflammatorymentioning
confidence: 99%